The Experiences of Specialist Nurses Working Within the Uro-oncology Multidisciplinary Team in the United Kingdom. Issue 4 (July 2017) - Punshon, Geoffrey; Endacott, Ruth; Aslett, Phillippa; Brocksom, Jane; Fleure, Louisa; Howdle, Felicity; Masterton, Morven; O'Connor, Anita; Swift, Adrian; Trevatt, Paul; Leary, Alison
Abstract : Purpose: United Kingdom prostate cancer nursing care is provided by a variety of urology and uro-oncology nurses. The experience of working in multidisciplinary teams (MDT) was investigated in a national study. Design: The study consisted of a national survey with descriptive statistics and thematic analysis. Methods: A secondary analysis of a data subset from a UK whole population survey was undertaken (n = 285) of the specialist nursing workforce and the services they provide. Data were collected on the experience of working in the MDT. Results: Forty-five percent of the respondents felt that they worked in a functional MDT, 12% felt that they worked in a dysfunctional MDT, and 3.5% found the MDT meeting intimidating. Furthermore, 34% of the nurses felt that they could constructively challenge all members of the MDT in meetings. Themes emerging from open-ended questions were lack of interest in nonmedical concerns by other team members, ability to constructively challenge decisions or views within the meeting, and little opportunity for patients' wishes to be expressed. Conclusions: Despite expertise and experience, nurses had a variable, often negative, experience of the MDT. It is necessary to ensure that all participants can contribute and are heard and valued. More emphasis should be given to patients' nonmedical needs.